Invitation to management - Lawrence, Peter A. (Oxford, Ox, UK ; New York, N.Y., U.S.A. : B. Blackwell, 1986)
The author looks frankly at the content and context of management and spells out what jobs in different areas of management, marketing, personnel, manufacturing, and so on are all about. The book includes a discussion on small firms and the problems of starting a business from scratch.
Includes index.
Includes bibliographical references p. 180-182 and index.
hza 06/08/2018
Loans
Keywords: Executive ability